A new reliable algorithm based on homotopy-perturbation method for power-law fin-type problems - Chowdhury, Md. Sazzad Hossien; Hassan, Talib Hashim (INSInet Publications, 2011)
In this paper, we applied the homotopy-perturbation method (HPM) to evaluate the temperature distribution of a straight rectangular fin with power-law temperature dependent surface heat flux. The time interval is divided into several subintervals and the HPM solutions are applied successively over these reduced time intervals. Comparisons between the 13-term HPM solution on a fixed time step and 6-term HPM solution on three different time steps are made. The results indicates that the obtained solution using different time step is quite accurate when only the six terms are used in the series expansion.